2023
DOI: 10.1021/acs.langmuir.2c03217
|View full text |Cite
|
Sign up to set email alerts
|

Porous Polymer Supported Amino Functionalized Ionic Liquid for Effective CO2 Capture

Abstract: A decrease in CO 2 emissions is urgently required in the present situation due to the fast growth of carbon dioxide (CO 2 ) in the atmosphere, which has caused a series of global climate issues. This study used an impregnation−evaporation method to immobilize an amino functionalized ionic liquid [C 2 OHmim][Lys] on a chromatographic column filler GDX-103 and create a novel supported ionic liquid. The results showed that the supported ionic liquid with 60 wt % ionic liquid content had the best adsorption perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…This resulted in a distinct structure compared to the bulk IL, which in turn enhanced the equilibrium sorption amount and rate. 8,42,43 As the sorption time progressed, the sorption rates of all of the samples decreased. This is primarily due to the high diffusion resistance of gas in the IL and micropores.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in a distinct structure compared to the bulk IL, which in turn enhanced the equilibrium sorption amount and rate. 8,42,43 As the sorption time progressed, the sorption rates of all of the samples decreased. This is primarily due to the high diffusion resistance of gas in the IL and micropores.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Among them, the composite of absorbents and adsorbents (i.e., absorbents combined with adsorbents) combines the advantages of both absorbent and adsorbent, and as reported, they can significantly improve the CO 2 sorption capacity and selectivity, as well as the sorption rate. , Currently, amines or ionic liquids (ILs) combined with solid adsorbents are common composites developed for CO 2 capture. Studies have shown that such composites can enhance the sorption capacity, rate, and selectivity of CO 2 . However, these materials commonly exhibit a trade-off of sorption amount and desorption heat. For example, the PEI/SiO 2 sorbent exhibited a CO 2 sorption of more than 1.39 mmol g –1 at 313 K, but the desorption heat was 100 kJ mol –1 .…”
Section: Introductionmentioning
confidence: 99%
“…Reactive separation has become an established method for CO 2 capture and has been widely used in industrial applications . Ongoing research continues to explore the effectiveness of new solvents, including ionic liquids and deep eutectic solvents, , as well as different solid sorbents such as zeolites, activated carbon, porous silica materials, and metal–organic frameworks. , Optimizing process conditions such as temperature, pressure, and solvent composition can enhance the performance and economics of reactive separation for CO 2 capture. In addition, a better understanding of the mechanisms underlying reactive separations offers valuable insights into the fundamental principles .…”
Section: Inaugural Topics For Virtual Special Issuesmentioning
confidence: 99%